Left Main Coronary Artery Thrombus Diagnosed and Managed With Coronary Computed Tomography Angiography and Fractional Flow Reserve Derived From Computed Tomography - Shone O Almeida; Nasih M Ahmed; Ronald P Karlsberg (Clinical Medicine Insights: Cardiology, 2019)
Left main coronary artery thrombus (LMCA-T) is a rare disease state and diagnosed with invasive coronary angiography (ICA). We present a case of LMCA-T diagnosed with coronary computed tomography angiography (CTA) and treated without ICA in a patient who presented to a hospital in the middle of war zone in Erbil, Iraqi Kurdistan. Coronary CTA performed 1 month later demonstrated resolution of the thrombus. Fractional flow reserve computed from computed tomography (FFR-CT; HeartFlow, Redwood City, CA) performed retrospectively confirmed that the clot was not hemodynamically significant at the time of diagnosis. This case demonstrates the diagnostic capabilities of coronary CTA and FFR-CT when ICA is not readily available.